Studi Kesesuaian Lahan Dan Pola Ruang Untuk Pengendalian Bencana Longsor Di Kabupaten Pohuwato - Nevi Kurniawati; Indriani Umar (JURNAL SAINS INFORMASI GEOGRAFI, 2025)
Landslides frequent in Pohuwato Regency are triggered by a combination of hilly topography, high rainfall intensity, and land use practices that are not in line with conservation principles. This study aims to analyze and map the spatial vulnerability to landslides and evaluate the suitability of existing spatial patterns in the Pohuwato Regency Spatial Plan (RTRW) document as a scientific basis for disaster mitigation strategies. The methods used are quantitative descriptive analysis and spatial modeling using the weighted overlay technique on a Geographic Information System (GIS) platform. Key parameters integrated include slope gradient, rainfall, soil type, and land use. The vulnerability mapping results show that areas with low, medium, and high landslide potential cover 58,570.66 ha, 65,810.38 ha, and 18,159.92 ha, respectively. The dominant factors contributing to high vulnerability are steep slope inclination, extreme rainfall, and land use transformation, particularly the conversion of forests into mining and settlement areas. An evaluation of the spatial compatibility between vulnerability maps and spatial patterns in the RTRW shows that, although the majority of spatial use planning is in line with disaster zoning, there are still settlements in high risk zones in several subdistricts, such as Taluditi, Patilanggio, Buntulia, Dengilo, and West Popayato. These findings highlight the importance of evaluating spatial planning policies and strictly enforcing land use regulations in order to reduce the risk of landslides.